Spontaneous closure of small apical muscular ventricular septal defects - Atalay, Semra; Tutar, Ercan; Ekici, Filiz; Naçar, Nazire (The Turkish Journal of Pediatrics, 2005)
Between 1993 and 2002, apical muscular ventricular septal defects were identified in 99 cases by echocardiographic examination. Spontaneous closure time was analyzed in 42 cases followed up at least two years, retrospectively. The ages of 42 cases ranged between 1 day and 13 years old. Initial examination was performed in 22 cases within the newborn period, in 8 cases between 1 and 6 months of age and in 12 cases at more than 6 months of age. Spontaneous closure was seen in 24 of 42 cases (57.1%) between 1 and 36 months of age, and it was most commonly recorded during the first 6 months. It was remarkable that spontaneous closure occurred in 20 of 22 cases (90%) diagnosed in the neonatal period. Closure was seen in 4 of 8 cases (50%) whose initial examination was performed between 1 and 6 months and in none of the patients diagnosed at more than 6 months of age. In conclusion, the frequency of spontaneous closure in cases diagnosed in the neonatal period is higher than previously believed. It is advisable to follow up patients to determine spontaneous closure, especially within the first two years of life.